Blurring Boundaries or Deepening Discourses on FoRB? From Global to Local and Back Again - Wilson, Erin K. (The review of faith & international affairs, 2022)
This article explores whether, and if so, how, vernacularization could play a role in fostering commitment to the right to freedom of religion or belief (FoRB) across different cultural and political contexts. It suggests that while there are indications that vernacularization could and does contribute to this goal, there are points of concern and aspects that remain under-researched. These lingering caveats relate to the process of vernacularization itself and to its specific application to the right to FoRB. Resolving these dilemmas requires sustained, active attention by scholars, policymakers, and advocates engaged in human rights research and implementation.